Effect of Pregnant Women's Fear of Covid-19 on Their Expectations, Experiences, and Reactions in The First Ultrasound Examination - Ebru Gözüyeşil; Ayseren Çevik; Cemile Onat Köroğlu; Rukiye Sülü Dursun; Şule Gökyıldız Surucu; Burcu Avcıbay Vurgeç (Journal of Midwifery, 2023)
This study aims to determine the effect of pregnant women’s fear of COVID-19 on their expectations, experiences, and reactions in the first ultrasound examination. This study was conducted with 166 pregnant women who visited the polyclinic in a Hospital of University, on the March and May, 2021 and, have an ultrasound examination for the first time. Data were collected using the Personal Information Form, the Fear of COVID-19 Scale (FCV-19S), and the Parents’ Expectations, Experiences, and Reactions to Routine Ultrasound Examination Scale (PEER-U). The average age of pregnant women was 29.02±5.56. While 15.1% had a COVID-19 positive history, 8.4% lost someone they knew due to COVID-19. FCV-19S score was found 18.26±5.32. Fear of COVID-19 scores were higher in women who did not work and who had their first pregnancy.  While the mean score for PEER-U before was 59.05±6.99, the mean score for PEER-U after was 65.07±4.53. While a positive correlation was reported between FCV-19S and the scores for PEER-U before (r=0.392), no significant correlation was detected between FCV-19S and the scores for PEER-U after.  Pregnant women were found to experience an average fear of COVID-19. It was found a correlation between COVID-19 and the scores for PEER-U before. The fear of COVID-19 and the scores for PEER-U before were found to be affected by some socio-demographic characteristics.